Centro de cultura e lazer no Beco do Macedo - Silveira, Júlia Cavalcante Linhares da (Brasil, 2024)
The present final graduation work arose with the existing problem in the city of Manaus, by the lack of spaces that encourage access to culture for the population to enjoy and at the same time because this access has a great importance in the development of society. With this the project has as main objective to encourage the access of culture and leisure by the population, through the creation of the project proposal of a Culture and Leisure Center located in the neighborhood Nossa Senhora das Graças, in an area commonly called in the city of Manaus. Providing a space that promotes the sociocultural development of individuals. In order to maintain public spaces, qualifying them for sports, leisure and cultural use, obtaining a certain relationship with the surroundings and at the same time meeting the demands of local residents.